The Proceedings of the International Conference on Sensing and Imaging - Jiang, Ming; Ida, Nathan; Louis, Alfred K.; Quinto, Eric Todd (Lecture Notes in Electrical Engineering, 2019)
This book collects a number of papers presented at the 2017 International Conference on Sensing and Imaging, held at Chengdu University of Information Technology. Sensing and imaging is an interdisciplinary field covering a variety of sciences and techniques such as optics, electricity, magnetism, heat, sound, mathematics, and computing technology. The field has diverse applications of interest such as sensing techniques, imaging, and image processing techniques. This book will appeal to professionals and researchers within the field. .